Animal : exploring the zoological world - Kingett, Lucy; Hanken, James; Piper, Ross.; Crumpton, Nick. (London : Phaidon Press Limited ; New York, NY : Phaidon Press Inc., 2018)
This book is a broad-ranging survey that explores and celebrates humankind's ongoing fascination with animals. Since our very first moments on Earth, we have been compelled to make images of the curious beasts around us--whether as sources of food, danger, wonder, power, scientific significance or companionship. This carefully curated selection of images, chosen by an international panel of experts, delves into our shared past to tell the story of animal life. From the first cave paintings, extraordinary medieval bestiaries and exquisite scientific illustration, to iconic paintings, contemporary artworks and the incredible technological advancements that will shape our futures together, the huge range of works reflects the beauty and variety of animals themselves--including butterflies, hummingbirds, bats, frogs, tigers, dogs, jellyfish, spiders and elephants. Arranged in a curated and thought-provoking sequence, this compilation includes iconic works by some of the great names in zoology, such as Conrad Gesner, Charles Darwin and John James Audubon, as well as celebrated artists and photographers, indigenous cultures and lesser-known figures who have made important contributions to the study and representation of animals throughout history.
Chiefly illustrations.
Formerly CIP.
boek